The image of the ideal world in the artistic culture of the Renaissance - Selitskii, Aleksandr L. (Human in the Socio-Cultural Dimension, 2023)
The notions of an ideal world in European Renaissance culture are considered. The general metaphysical foundations of the epoch, most clearly expressed in neoplatonism, are revealed. The relationship is shown between the philosophical interpretation of the earthly world as an emanation of the higher principle (the one, the absolute) and the search for an ideal form of beauty in art that can most fully convey the perfection of the creator of all that exists. Hence, the artistic reflection of reality, both social and natural, appears not just as a «cast» from nature, but acts, first of all, as a project of a man-demiurge who strives to visually embody his own understanding of divine harmony. It is noted that in the literature and painting of the European Renaissance, the «ideal world» is most often represented by universal images of possible being, transcendent in its essence to earthly reality. Against the background of the general spiritual tendencies of the Renaissance, the features of the Belarusian culture of this period are analysed. It is argued that in domestic philosophical thought and art, ideas about the ideal world, perfect social being are inextricably linked with the image of the native land. The main attention of the figures of the Belarusian Renaissance was aimed at improving society and the state, existing socio-political and legal institutions. In literature (F. Skorina, М. Hussowczyk, etc.), the image of the native land, its nature, and the heroic past were elevated. The immanence of the ideal world model to earthly existence is considered as a characteristic feature of the Belarusian culture, revealing the originality of the national world view.